2016
DOI: 10.1007/s00438-015-1155-y
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone pathway genes and plant architecture: association analysis and QTL detection for horticultural traits in chrysanthemum

Abstract: Chrysanthemums are important ornamental plants with abundant phenotypic diversity. Especially in cut-flower breeding, shoot branching is important for the success of new varieties. To assess the genetic regulation of shoot branching and other horticultural important traits, we phenotyped and genotyped two types of chrysanthemum populations: a genotype collection of 86 varieties and a biparental F1-population (MK11/3) of 160 individuals. Using two different statistical approaches, a genome-wide association anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In recent years, genome-wide association studies (GWASs) based on linkage disequilibrium have been shown to represent a powerful tool for detecting important QTLs or genes underlying complex traits in the sequenced genomes of rice 14 , Arabidopsis thaliana 15 , and maize 16 and the unsequenced genomes of wheat 17 and roses 18 . In chrysanthemums, GWASs have been used to identify favorable alleles and to explore the pattern of inheritance for a number of horticultural and WT traits based on gel-based markers 7,19,20 . However, the low marker density exhibited in the traditional molecular marker system limits the detection power of GWASs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, genome-wide association studies (GWASs) based on linkage disequilibrium have been shown to represent a powerful tool for detecting important QTLs or genes underlying complex traits in the sequenced genomes of rice 14 , Arabidopsis thaliana 15 , and maize 16 and the unsequenced genomes of wheat 17 and roses 18 . In chrysanthemums, GWASs have been used to identify favorable alleles and to explore the pattern of inheritance for a number of horticultural and WT traits based on gel-based markers 7,19,20 . However, the low marker density exhibited in the traditional molecular marker system limits the detection power of GWASs.…”
Section: Introductionmentioning
confidence: 99%
“…In chrysanthemum, Klie et al (2016) have used GWAS to identify a number of AFLP markers and candidate gene-related alleles associated with shoot branching traits and Li et al (2016) have uncovered considerable dominant markers linked to certain plant and inflorescence traits. The present attempt was based on a large collection of SNP assays, so was more informative than the Li et al (2016) study, which worked with a very limited number of gel-based markers.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been used to dissecting genetic basis of quantitatively inherited traits in a number of plant species (Huang et al 2010; Kump et al 2011; Morris et al 2013; Zhang, Song, et al 2014). The use of GWAS to date in chrysanthemum has been restricted to the genetic analysis of a few horticultural traits (Klie et al 2016; Li et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Several candidate genes related to waterlogging tolerance and inflorescence-related traits were recently identified based on the above-mentioned SNP sets in a similar way 99,100 . Using another method, Klie et al 101 were able to identify 11 markers significantly associated with four strigolactone pathway genes regulating shoot branching in chrysanthemum by utilizing the candidate gene approach, which also provided insight into some potential candidate genes.…”
Section: Molecular Breedingmentioning
confidence: 99%